Potential of diacylglycerol to replace nature fats in conventional plastic fats: preparation, purification, functionalities and applications - Xie, Pengkai; Mao, Yilin; Zou, Shuo; Ke, Wanting; Lee, Yee Ying; Tan, Chin Ping; Wang, Yong; Zhang, Zhen (Elsevier, 2025)
Background: Plastic fat, a lipid mix of oil and solid fat, is crucial in food specialty fat system. Its spreadability depends on crystallization, crystal shape, melting point, and solid fat content (SFC). Traditional triacylglycerol (TAG) requires hydrogenation to achieve the desired application characteristics, a process that can generate unhealthy trans fatty acids, while TAG-based plastic fats are often high in saturated fatty acids, posing potential health risks. Diacylglycerol (DAG) serves as a healthier substitute for saturated TAG, and improved texture stability. However, there is a lack of systematic reviews on the mechanistic exploration of the application of DAG in plastic fats. Scope and approach: This contribution aimed to explore the synthesis and preparation of DAG over the past 36 years, focusing on its application mechanism in plastic fat as an additive and main component. Additionally, this review evaluated its advantages, challenges, and future directions in replacing saturated TAG. Key findings and conclusions: The molecular structure similarity between DAG and TAG enables the former to significantly impact the crystallization behavior of plastic fat, leading to the formation of products with the desired characteristics. However, DAG content is generally low in natural oils, emphasizing the significance of the preparation and purification of DAG to develop plastic fats. This review systematically examines how DAG affects plastic fat crystallization as both an emulsifier and a structural component. It is established that DAG can replace TAG as the primary component and be used to manufacture healthy plastic fats for application in food specialty fat system.